Amorfização e cristalização da liga fe68cr8mo4nb4b16: caracterização através de técnicas avançadas de microscopia eletrônica - Coimbrão, Diego Davi (2019)
Stainless steels of the different classes can have their composition modified through the addition of boron, aiming to obtain both amorphous phases and the controlled formation of borides. The formation of amorphous phase and the controlled formation of borides have the objective to optimize surface properties, specifically, the corrosion resistance and the wear resistance. Depending on the system, the composition and the processing route, borides can be formed in different stages, such as, during solidification by precipitation from solid crystalline phases or during the crystallization of an amorphous matrix. In each case, borides with different crystalline structures and different compositions can be formed. This present project had the objective to produce, via different processing routes, a new Fe-based alloy with composition, Fe68Cr8Mo4Nb4B16, and to characterize the phases formed through the techniques of x-ray diffraction, electron diffraction, EDS, EELS and ASTAR. The alloy with microstructure near the equilibrium was produced by arc melting, and from this master alloy, amorphous alloys were produced by rapid solidification by the melt-spinning technique. Detailed microstructural characterization was performed in all conditions of processing; in the crystalline alloy produced by arc melting, in the amorphous alloys produced by melt-spinning and in the partially and fully crystallized alloys produces by controlled heat treatments of the amorphous ribbons. For the alloys crystallized from the amorphous phase, the results indicated the formation of phases, different from the equilibrium, and also different sequences of formation. Specifically, the amorphous alloys crystallize in the following sequence: [am + Chi-phase + M23B6] → [am + Chi-phase + M23B6 + Fe-alpha] → [Fe-alpha + MB + M2B tetragonal + M2B orthorobic + M3B2 + MB2 + M23B6]. Finally, the Fe68Cr8Mo4Nb4B16 alloys processed by the different routes were characterized electrochemically in acidic and alkaline media, indicating outstanding high corrosion resistance of the new glassy alloy, justified by the amorphous nature and the presence of corrosion resistant alloying elements such as chromium and molybdenum.